In vivo Functional Genomics for Undiagnosed Patients: The Impact of Small GTPases Signaling Dysregulation at Pan-Embryo Developmental Scale - Lauri, Antonella; Fasano, Giulia; Venditti, Martina; Dallapiccola, Bruno; Tartaglia, Marco (Frontiers in Cell and Developmental Biology, 2021)
While individually rare, disorders affecting development collectively represent an important clinical, psychological and socio-economic burden to patients, families and society. Insights into the molecular mechanisms underlying these disorders are required to speed up diagnosis, improve counseling and optimize management towards targeted therapies. Genome sequencing is now unveiling previously unexplored genetic variations in undiagnosed patients, which requires functional validation and mechanistic understanding, particularly when dealing with novel nosologic entities. Functional perturbations of key regulators acting on signals’ intersections of evolutionary conserved pathways hinder the fine balance between various developmental inputs governing morphogenesis and homeostasis. However, the distinguishing mechanisms by which these hubs orchestrate pathways to ensure the developmental coordinates is poorly understood. Integrative functional genomics implementing quantitative in vivo models of embryogenesis with subcellular precision in whole organisms contribute to answering these questions. Here, we review the current knowledge on the genes and mechanisms critically involved in developmental syndromes and pediatric cancers, revealed by genomic sequencing and in vivo models in insects, worms and fish. We focus on the monomeric GTPases of the RAS superfamily and their influence on crucial developmental signals and events. We next discuss the effectiveness of exponentially growing functional assays employing tractable models to identify regulatory crossroads. Unprecedented sophistications are now possible in zebrafish, i.e. genome editing with single nucleotide precision, nanoimaging, highly resolved recording of multiple small molecules activity as well as simoultaneous monitoring brain circuits and complex behavioral response. These assets permit accurate real-time reporting of dynamic small GTPases-controlled processes in entire organisms, owning the potential to tackle rare disease mechanisms.